Latin American Education in Perspective: Learning Experiences, Territory, and Human Rights: Educación Latinoamericana en Perspectiva: Experiencias Formativas, Territorio y Derechos Humanos (Papeles, 2025)
The Special Issue of the Papeles Journal, "Relevant Experiences in Education from a Latin American Perspective" is dedicated to education in Latin America, with special emphasis on learning strategies, the role of technology, inclusive education, social education, and human rights education.The works gathered in this issue have been written across different latitudes of the region and share a common interest in and commitment to education. Moreover, these works acknowledge that educational institutions have an unavoidable commitment to democracy and the construction of an engaged, critical, and socially responsible citizenry. The development of critical thinking, the promotion of social sensitivity, and empathy toward others are objectives of the entire educational system, as reflected in the concrete experiences described in the texts within this volume.
Keywords: Latin American Education; Learning Experiences; Critical Education